The modular compilation of effects - Day, Laurence E. (2017)
The introduction of new features to a programming language often requires that its compiler goes to the effort of ensuring they are introduced in a manner that does not interfere with the existing code base. Engineers frequently find themselves changing code that has already been designed, implemented and (ideally) proved correct, which is bad practice from a software engineering point of view.